Ideology representation in the editorial of Koran Tempo and Kompas on COVID-19 handling in Indonesia - Bakdal Ginanjar; Chattri Sigit Widyastuti; Sumarlam Sumarlam (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Ideology representation in the editorial of Koran Tempo and Kompas on COVID-19 handling in IndonesiaThis article examines the editorials in Koran Tempo and Kompas in representing their ideology of COVID-19 handling in Indonesia. This linguistic research is conducted qualitatively. The data were in the form of Indonesian-language editorial discourse, which discussed the COVID-19 handling in Indonesia. The written research data were taken from national newspapers, namely Koran Tempo and Kompas, and were obtained through the use of listening and note-taking techniques. They were then analyzed using Van Dijk’s critical discourse analysis model. The results of the analysis show that there are differences in the representation of ideology in Koran Tempo and Kompas on COVID-19 handling in Indonesia through their editorials that are systematically constructed in microstructure, superstructure, and macrostructure. In the microstructure, ideology is realized through the lexicon, specifically the use of the dominant persona, use of syntactic structures in the form of active-passive sentences, affirmative sentences, and imperative sentences, as well as the use of repetition styles and metaphors. Koran Tempo uses ideological patterns as actions and ideology beliefs in its superstructure. Meanwhile, Kompas uses ideological patterns as systems of thought and systems of action. The difference between the microstructure and the superstructure results in a different macrostructure. Koran Tempo portrays government as the key stakeholder in handling COVID-19 in Indonesia. Meanwhile, Kompas’ editorial was directed at how the handling of COVID-19 was done through communal actions. The Koran Tempo ideology underlines who has a role in handling COVID-19, while the Kompas ideology focuses at what needs to be done in handling COVID-19.Keywords: critical discourse analysis, editorial discourse, ideology, COVID-19Representasi ideologi dalam tajuk Koran Tempo dan Kompas tentang penanganan COVID-19 di IndonesiaArtikel ini mengkaji perihal bagaimana tajuk pada Koran Tempo dan Kompas merepresentasikan ideologinya tentang penanganan COVID-19 di Indonesia. Penelitian ini berjenis kualitatif dalam bidang linguistik. Data yang dianalisis berbentuk wacana tajuk berbahasa Indonesia yang berisi tentang penanganan COVID-19 di Indonesia. Sumber data penelitian berwujud tertulis yang diambil dari surat kabar nasional: Koran Tempo dan Kompas. Metode simak dan teknik catat dilakukan untuk mengumpulkan data. Model analisis wacana kritis dari Van Dijk diterapkan untuk menganalisis data. Hasil analisis menggambarkan adanya perbedaan representasi ideologi Koran Tempo dan Kompas tentang penanganan COVID-19 di Indonesia melalui tajuk yang dikonstruksi secara sistematis dalam struktur mikro, super struktur, dan struktur makro. Dalam struktur mikro, ideologi direalisasikan melalui leksikon, khususnya penggunaan kata persona yang dominan, penggunaan struktur sintaksis berupa kalimat aktif-pasif, kalimat berita, dan kalimat perintah, serta penggunaan gaya repetisi dan metafora. Koran Tempo menggunakan pola ideologi sebagai tindakan dan ideologi sebagai keyakinan dalam super strukturnya. Sebaliknya, Kompas menggunakan pola ideologi sebagai sistem pemikiran dan sistem tindakan. Perbedaan struktur mikro dan super struktur tersebut menghasilkan struktur makro yang berbeda pula. Koran Tempo mengangkat tema tentang pemerintah sebagai aktor kunci dalam penanganan COVID-19 di Indonesia. Sementara itu, tema tajuk Kompas diarahkan pada penanganan COVID-19 yang dilakukan dengan berbagai tindakan secara bersama-sama. Ideologi Koran Tempo mengarah pada siapa yang berperan dalam penanganan COVID-19, sedangkan ideologi Kompas mengarah pada apa yang perlu dilakukan dalam penanganan COVID-19. Kata kunci: analisis wacana kritis, wacana tajuk, ideologi, COVID-19